2020
DOI: 10.26613/jca/3.2.56
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Vandalism, Historical Distortion: The Labour Antisemitism Crisis and the Limits of Class Instrumentalism

Abstract: Through secondary analysis of survey data collected by YouGov for Campaign Against Antisemitism, this research note provides a longitudinal account of changes in Judeophobic antisemitism (that is, antisemitism articulated in relation to Jews identified as Jews) in mainland Britain from 2016-2020. Because survey responses are aggregated by most recent general election vote, the dataset facilitates comparison between those who voted for each of Britain’s three main parties in the 2015, 2017, and 2019 UK general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In the 1980s, it was observed that the antisemitism of British far-right leaders brought them no political advantage, having little appeal to members of the communities within which they sought to recruit followers (Billig, 1988), and it has since been argued that a reorientation around anti-Muslim (as opposed to anti-Jewish) agitation has been key to recent electoral gains by radical right-wing parties in Europe (Berntzen, 2020). Moreover, since the 1980s, the influence of antisemitic ideas on the far left has emerged as a concern for many scholarly observers (Billig, 1984a, b;Bolton, 2020;Fine and Spencer, 2017;Hirsh, 2007;Johnson, 2019;Julius, 2010;Rich, 2018Rich, [2017), and an argument has been made that conspiracy narratives used by both right-and left-wing populists possess an inherent potential for linkage with antisemitism (Bolton and Pitts, 2018, pp. 214-219): as one observer puts it, contemporary antisemitism transcends the ideological differences associated with 'opposite ends of the political continuum … by travelling … through the connective tissues of enduring tropes' (Elman, 2022, p. 112).…”
mentioning
confidence: 99%
“…In the 1980s, it was observed that the antisemitism of British far-right leaders brought them no political advantage, having little appeal to members of the communities within which they sought to recruit followers (Billig, 1988), and it has since been argued that a reorientation around anti-Muslim (as opposed to anti-Jewish) agitation has been key to recent electoral gains by radical right-wing parties in Europe (Berntzen, 2020). Moreover, since the 1980s, the influence of antisemitic ideas on the far left has emerged as a concern for many scholarly observers (Billig, 1984a, b;Bolton, 2020;Fine and Spencer, 2017;Hirsh, 2007;Johnson, 2019;Julius, 2010;Rich, 2018Rich, [2017), and an argument has been made that conspiracy narratives used by both right-and left-wing populists possess an inherent potential for linkage with antisemitism (Bolton and Pitts, 2018, pp. 214-219): as one observer puts it, contemporary antisemitism transcends the ideological differences associated with 'opposite ends of the political continuum … by travelling … through the connective tissues of enduring tropes' (Elman, 2022, p. 112).…”
mentioning
confidence: 99%